An Evaluation of the Relationship between Pre-service Teachers’ Critical Thinking Dispositions and Democratic Values in Terms of Critical Pedagogy - Uluçınar, Ufuk; Aypay, Ahmet (Journal of History Culture and Art Research, 2018)
The purpose of this study was to investigate the relationship between critical thinking dispositions and democratic values among pre-service teachers. Accordingly, we examined whether pre-service teachers’ critical thinking dispositions predicted the presence of democratic values. We emphasized the role of critical consciousness in the development of an understanding of democracy with respect to individual educational experiences with the assumption that people who think critically are more likely to have democratic values. The study group consisted of pre-service teachers from six departments within the Faculty of Education at a public university in Turkey. The data were collected using the Critical Thinking Dispositions Instrument, which was developed by researchers; the Pre-Service Teachers Democratic Values assessment, which was developed by Selvi (2006) and a Personal Information Form. The data were analyzed using descriptive statistics, Product-Moment Correlations and Multiple Regression Analysis Techniques. The findings indicated a significant correlation between critical thinking dispositions and democratic values among pre-service teachers. In addition, the critical dispositions of pre-service teachers predicted democratic values. Therefore, it may be useful for pre-service teachers to engage in activities that enhance critical thinking and awareness of democratic values.